Novel Non-invasive Fractional Flow Reserve from Coronary CT Angiography to Determine Ischemic Coronary Stenosis - Lavanya Cherukuri; Divya Birudaraju; Matthew J Budoff (US Cardiology Review)
Coronary artery disease (CAD) patients may have an obstructive disease on invasive coronary angiography, but few of these patients have had flow-limiting obstructive disease diagnosed on invasive fractional flow reserve (FFR). FFR is infrequently performed because of its cost- and time-effectiveness. Advancement in non-invasive imaging has enabled FFR to be derived non-invasively using coronary CT angiography (CCTA), without the need for induction of hyperemia or modification of the standard CCTA acquisition protocol. FFR derived from CCTA (FFRCT) has been shown to have excellent correlation with invasive FFR, and remains an effective diagnostic tool in the presence of reduced signal-to-noise ratio, coronary calcification and motion artifact. The utility of FFRCT has also helped to deepen our understanding of hemodynamically significant CAD. Hence, there is now interest in exploring the possible interplay between these mechanistic forces and their effect on the development of coronary plaque and the vulnerability of these plaques.